2017
DOI: 10.1007/s13592-016-0486-y
|View full text |Cite
|
Sign up to set email alerts
|

Antennal sensilla of cleptoparasitic and non-parasitic bees in two subfamilies of Apidae

Abstract: -In bees, most of the comparative studies linking the sensory system and behavior were performed in social species. Here, we describe the morphology of antennal sensilla in solitary and cleptoparasitic bees of Apinae and Nomadinae. The external and internal structure of sensilla and setae as well as their distribution in flagella were studied in detail in two different host-cleptoparasitic associations. In addition, taking into account the presence of pores, the distribution of sensilla was compared in females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Sensilla length was measured using the Image ProPlus 4.5 program (Ravaiano et al , ). We chose to study the dorsal surface of the antennae of T. fiebrigi because, as previously reported for other bees, sensilla are present in higher numbers and are more diverse on the dorsal surface of the appendage (Ravaiano et al , ; González‐Vaquero & Galvani, ; Carvalho et al , ; Galvani et al , ). In our case, there were fewer sensilla (two types of both sensilla trichodea and sensilla placodea) on the ventral surface of the antennae than in the dorsal surface, and only one subtype of sensilla trichodea on the pedicel of all classes of individuals of T. fiebrigi (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Sensilla length was measured using the Image ProPlus 4.5 program (Ravaiano et al , ). We chose to study the dorsal surface of the antennae of T. fiebrigi because, as previously reported for other bees, sensilla are present in higher numbers and are more diverse on the dorsal surface of the appendage (Ravaiano et al , ; González‐Vaquero & Galvani, ; Carvalho et al , ; Galvani et al , ). In our case, there were fewer sensilla (two types of both sensilla trichodea and sensilla placodea) on the ventral surface of the antennae than in the dorsal surface, and only one subtype of sensilla trichodea on the pedicel of all classes of individuals of T. fiebrigi (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…With the goal of finding characters that allow differentiation of the new species of Lasioglossum (Dialictus), the different sensilla on the antenna of females from these taxa were examined. Sensilla variation has been found to be useful for discrimination of parasitic bees (Wcislo 1995;Galvani et al 2016). The following types of sensilla are recognized in species of Lasioglosum (Dialictus): stA, stB, stC, stD, sPa, sCoe, sAmp, Scap value and setae (Fig.…”
Section: Antenna Sensillamentioning
confidence: 99%
“…They play an important role in insect life behaviors, such as habitat selection, food searching, mating, oviposition sites, and intraspecific and interspecific recognition [ 3 , 4 , 5 , 6 ]. Previous studies have shown that the type and distribution of sensilla in antennae are related to sex [ 7 , 8 , 9 ], feeding [ 10 , 11 ], and whether they sojourned [ 12 , 13 ], which are decided at the stage of insect morphogenesis [ 14 , 15 ]. Even the types, numbers, and distribution of antennal sensilla are diverse in different castes in the same species [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%